Supersymmetric indices of 3d S-fold SCFTs - Ivan Garozzo; Gabriele Lo Monaco; Noppadol Mekareeya; Matteo Sacchi (Journal of High Energy Physics, 2019)
Abstract Enhancement of global symmetry and supersymmetry in the infrared is one of the most intriguing phenomena in quantum field theory. We investigate such phenomena in a large class of three dimensional superconformal field theories, known as the S-fold SCFTs. Supersymmetric indices are computed for a number of theories containing small rank gauge groups. It is found that indices of several models exhibit enhancement of supersymmetry at the superconformal fixed point in the infrared. Dualities between S-fold theories that have different quiver descriptions are also analysed. We explore a new class of theories with a discrete global symmetry, whose gauge symmetry in the quiver has a different global structure from those that have been studied earlier.